Retraction Note: Calycosin-7-O-β-D-glucoside promotes oxidative stress-induced cytoskeleton reorganization through integrin-linked kinase signaling pathway in vascular endothelial cells - Yue-Hua Jiang; Wei Sun; Wei Li; Hong-Zhen Hu; Le Zhou; Hui-Hui Jiang; Jing-Xin Xu (BMC, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12906-015-0839-5.